2008
DOI: 10.1001/archoto.2007.4
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Temporal Bone Computed Tomographic Measurements in the Evaluation of Inner Ear Malformations

Abstract: Inner ear measurements in children with and without SNHL are not statistically different. Moreover, the measurements are difficult to interpret because while they demonstrate good reproducibility, they are susceptible to systematic biases. However, use of inner ear measurements is more sensitive in identifying vestibulocochlear dysplasias and should be considered to complement visual analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 18 publications
(26 reference statements)
1
24
1
Order By: Relevance
“…Our cochlear measurements are within the range of inner ear measurements reported in the literature in fetuses (20), children (21,23,26), and adults (6). As our youngest fetus was aged 21 WA, our data suggest that adult size is reached at or before 21 WA.…”
Section: Inner Ear Bony Developmentsupporting
confidence: 84%
“…Our cochlear measurements are within the range of inner ear measurements reported in the literature in fetuses (20), children (21,23,26), and adults (6). As our youngest fetus was aged 21 WA, our data suggest that adult size is reached at or before 21 WA.…”
Section: Inner Ear Bony Developmentsupporting
confidence: 84%
“…4). On the other hand, in their radiologic study, Chen et al (24) reported the mean BTC lumen to be 1.7 T 0.2 mm, and in their study on corrosion casts, Erixon et al (4) found that the internal diameter of the BTC varied from 1.6 to 2.6 mm. Previous studies do not mention the site at which the diameter was measured.…”
Section: Discussionmentioning
confidence: 95%
“…Measurement of the width of the central bony islands of the superior and lateral semicircular canals on axial high-resolution CT images has been proposed as a means for identifying any subtle abnormalities of the semicircular canals that may exist in children with congenital sensorineural hearing loss whose inner ear anatomy appears normal on CT and MR images (18,19).…”
Section: Malformations Of the Vestibule And Semicircularmentioning
confidence: 99%